Aging and Senescence in Canine Testes. Issue 5 (September 2019) - Merz, Sophie E.; Klopfleisch, Robert; Breithaupt, Angele; Gruber, Achim D.
Senescent cells accumulate with age but tissue-based studies of senescent cells are limited to selected organs from humans, mice, and primates. Cell culture and xenograft studies have indicated that senescent cells in the microenvironment may play a role in tumor proliferation via paracrine activities. Dogs develop age-related conditions, including in the testis, but cellular senescence has not been confirmed. We hypothesized that senescent cells accumulate with age in canine testes and in the microenvironment of testicular tumors. We tested the expression of the established senescence markers γH2AX and p21 on normal formalin-fixed, paraffin-embedded testes from 15 young dogs (<18 months of age) and 15 old dogs (7–15 years of age) and correlated the findings with age-dependent morphological changes. A statistically significant age-dependent increase in the percentage of p21-expressing cells was observed for testicular fibroblasts (4-fold) and Leydig cells (8-fold). However, p21-expressing cells were still a rare event. In contrast, the percentage of γH2AX-positive cells did not increase with age. P21- and γH2AX-expressing cells were rare in the microenvironments of tumors. Age-dependent morphological changes included an increased mean number of Leydig cells per intertubular triangle (2.95-fold) and a decreased spermatogenesis score. To our surprise, no age-related changes were recorded for interstitial collagen content, mean tubular diameter, and epithelial area. Opposed to our expectations based on previous in vitro data, we did not identify evidence of a correlation between age-associated accumulation of senescent cells and testicular tumor development. Understanding the role of the microenvironment in senescence obviously remains a challenging task.